TO STUDY THE EFFECT OF KUTAJA GHANA IN ATISAR VEGAVASTHA (ACUTE DIARRHEA) - Nileema Raju, Shisode (International Journal of Ayurveda and Pharma Research, 2016)
Diarrhea is a major disease in India. To avoid heavy economic burden for its treatment it is necessary to introduce a drug which is easily available, also cost effective and having quick result. So Kutaja Ghana is made as drug prepared by method given in Rasoddhar tantra. We found that percentage of total alkaloids increased after preparation of Kutaja Ghana. Connesine is active ingredient of Kutaja, its confirmation done by NMR and mass index study. Chromatograph of chloroform soluble extract of Kutaja powder shows 55.32% of connesine and that of Kutaja Ghana shows 99.10% of connesine. Also clinical trial of 60 patients confirmed its efficacy to treat diarrhea. Random selection of 60 patients from IPD or OPD of Ayurveda seva sangha hospital Nashik had done. 250 mg three times a day was the dose of group A patients treated with Kutaja ghana. Duration of treatment was three days. Group B was treated with Sanjivani vati 250mg three times a day. Thus probability of occurrence of value obtained by chance is much less than 0.05, the critical of 5%level of significance. The difference is real in 98% experiments hence highly significant. Statistical Analysis of the Data to Verify Difference Between the Effect of Drugs Kutaja Ghana and Sanjivani vati.